Here's the question you clicked on:

55 members online
  • 0 replying
  • 0 viewing

BrennaM

  • 3 years ago

-1/3x = 12

  • This Question is Closed
  1. nissn
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 1

    -1/3 =12 (-1/3x)*3=12*3 -3/3x=36 -x = 36 x=-36

  2. gerryliyana
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    take it the simple way -1/3x = 12 -1 = 12 . 3x -1 = 36x x = -1/36

  3. gerryliyana
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    @nissn why -36??? are you sure??

  4. gerryliyana
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    the result is -1/36 @BrennaM

  5. nissn
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 1

    i think it was -(1/3)*x = 12 which is x= -36 i wrote it wrong though -(1/3)*x = 12 -x=12/(1/3) -x=36 x=-36

  6. gerryliyana
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    do you sure -(1/3)x and not -1/3x???

  7. gerryliyana
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    in the question there is no brackets

  8. nissn
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 1

    @BrennaM was it -(1/3)*x=12 or -(1/3x)=12

  9. BrennaM
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    idk It was a test

  10. Not the answer you are looking for?
    Search for more explanations.

    • Attachments:

Ask your own question

Sign Up
Find more explanations on OpenStudy
Privacy Policy